Beneficiary participation in enhanced people's housing process (EPHP) projects in rural communities of Chris Hani district, Eastern Cape province - Njikelana, Phaphama Helena (My University, 2019)
Community participation is one of the sustainable human settlement’s focuses, intended to guarantee that communities are an integral part that determines the design, implementation and out of the programmes in relation to their developmental needs. Community participation empowers the community members through skills development and capabilities which enables them to negotiate and make appropriate decisions for their development. In South Africa, Enhanced People’s Housing Process (EPHP) is one policy that enforces this. However community participation especially in project implementation is not without challenges. The research was aimed at assessing the extent of beneficiary participation in Enhanced People Housing Process (EPHP) in rural Eastern Cape. The study focused on the case study of Zwart Water and Lubisi Villages in the Chris Hani District, where the EPHP (the forerunner of the EPHP) programme is being implemented. The research drew from literature on the development of EPHP in South Africa, self-help housing and community driven development. A qualitative research method was adopted and both primary and secondary data collection techniques were adopted. The study revealed that despite policy assertion putting beneficiaries as drivers of the EPHP, the actual implementation of EPHP clearly shows a disjuncture between policy interface and actual implementation. The majority of the beneficiaries did not have a full control of their projects and have decision making in the initiation, planning and implementation stages of their houses constructions. The study further revealed that the EPHP in both villages is externally driven, top down managed and private contractors/developers driven against the people driven approach as stipulated by the EPHP policy guidelines. The main finding is that beneficiaries only participated as general labourers for a wage during their actual housing construction and were not directly involved in decision making concerning the building plans and other EPHP process. It is therefore recommended that all level of government should ensure strong commitment to community participation in programme implementation as stipulated by the policy
A Research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg in partial fulfillment of the requirements for the degree of Masters of the Built Environment. Johannesburg, 2019